2009
DOI: 10.1111/j.1462-5822.2008.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale identification ofLegionella pneumophilaDot/Icm substrates that modulate host cell vesicle trafficking pathways

Abstract: SummaryThe bacterial pathogen Legionella pneumophila replicates in a specialized vacuole within host cells. Establishment of the replication vacuole depends on the Dot/Icm translocation system that delivers a large number of protein substrates into the host cell. The functions of most substrates are unknown. Here, we analysed a defined set of 127 confirmed or candidate Dot/Icm substrates for their effect on host cell processes using yeast as a model system. Expression of 79 candidates caused significant yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
169
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 74 publications
11
169
0
1
Order By: Relevance
“…It was previously shown, using effectors from various pathogenic bacteria, including C. burnetii and L. pneumophila, that ectopic expression of effectors sometimes results in inhibition of yeast growth (21,25,32,33,67,68). Yeast growth inhibition suggests that a conserved and essential eukaryotic process that is modulated by the effector in the host cell was also modulated in the yeast cell, resulting in inhibition of yeast cell growth (33,34,67,69). Examination of the 13 newly identified C. burnetii effectors (CBU0062, CBU0113, CBU0978, CBU1063, CBU1370, CBU1387, CBU1409, CBU1634a, CBU1676, CBU1794, CBU1818, CBU2007, and CBU2013) in yeast revealed that all of them were expressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown, using effectors from various pathogenic bacteria, including C. burnetii and L. pneumophila, that ectopic expression of effectors sometimes results in inhibition of yeast growth (21,25,32,33,67,68). Yeast growth inhibition suggests that a conserved and essential eukaryotic process that is modulated by the effector in the host cell was also modulated in the yeast cell, resulting in inhibition of yeast cell growth (33,34,67,69). Examination of the 13 newly identified C. burnetii effectors (CBU0062, CBU0113, CBU0978, CBU1063, CBU1370, CBU1387, CBU1409, CBU1634a, CBU1676, CBU1794, CBU1818, CBU2007, and CBU2013) in yeast revealed that all of them were expressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main secretion system of Legionella, essential for intracellular growth, is the type IVB Dot/Icm secretion system (Marra and Shuman 1992;Berger and Isberg 1993). Using many dif-ferent methods it has been shown that at least 275 L. pneumophila proteins are secreted by this system (Campodonico et al 2005;de Felipe et al 2005;Shohdy et al 2005;de Felipe et al 2008;Burstein et al 2009;Heidtman et al 2009;Zhu et al 2011), which represents nearly 10% of the protein-coding genes predicted in the L. pneumophila genomes. At least 75 of these are eukaryotic-like proteins or carry eukaryotic domains and, for certain of these, it has also been shown experimentally that they interfere with host-cell signaling pathways ( Table 2).…”
Section: Eukaryotic-like Proteins Of Legionella Are Virulence Factorsmentioning
confidence: 99%
“…The bacterium Legionella pneumophila is a prominent example, and a large amount of research has been performed on the mechanisms and proteins involved in evasion of lysosomal degradation (10). After Legionella is taken up by the cell into a Legionella-containing vacuole (LCV), the bacterium injects more than 250 proteins into the host cell using a type IV secretion system termed DOT/ICM (defect in organelle trafficking/intracellular multiplication) (11,12). Several of these proteins have been observed to modify Rab1 function, i.e.…”
mentioning
confidence: 99%
“…Amino acids 1-339 represent the adenylyltransferase domain, amino acids 340 -533 represent the GEF domain, and amino acids 534 -647 represent the phosphatidylinositol-4-phosphate binding domain (P4M) of DrrA, respectively. The catalytic motif GX 11 DXD of the adenylyltransferase domain of DrrA (Fig. 2B, indicated by a red arrow) is quite far from the GEF binding site of Rab1, and on the opposite side of DrrA (Fig.…”
mentioning
confidence: 99%